Functional Investigation of OXPHOS assembly factors in Leber’s Hereditary Optic Neuropathy - Fonseca, Maria Inês Arêlo Manso da (2016)
FONSECA, Maria Inês Arêlo Manso da - Functional Investigation of OXPHOS assembly factors in Leber’s Hereditary Optic Neuropathy. Coimbra : [s.n.], 2016. Dissertação de Mestrado